Mapping of Destructive Tectonic Earthquakes in the West Nusa Tenggara (NTB) Region Based on the Zhao Attenuation Function - Luthfin, Ahmad; Irjan, Irjan; Hidayati, Septiana Nur (Jurnal Penelitian Fisika dan Aplikasinya (JPFA), 2022)
NTB is a group of small islands located between the earthquake zone, namely in the south there is a subduction zone of the Eurasian and Indo-Australian plates and in the north, there is a back-arc fault or Flores Thrust. Earthquakes in this area are very active in the form of shallow tectonic earthquakes of large magnitude, so the risk of disaster is very high. Based on this, our research aims to map the distribution of destructive earthquakes using the attenuation function Zhao, released in 2006. The Zhao attenuation function has been applied to earthquake sources in subduction zones which are inputs for seismic hazards in various parts of the world, because the distance uncertainty factor used has better accuracy. The distribution of earthquake epicenter points in the West Nusa Tenggara region is clustered in four places, namely the Eurasian and Indo-Australian plate subduction zones in the sea south of the West Nusa Tenggara islands, the non-volcanic zone to the south of the West Nusa Tenggara islands, the volcanic zone to the east, and the Back Arc Thrust zone in the waters north of the NTB islands. Meanwhile, the hypocenter distribution is spread majorly on the Eurasian plate. Most of the islands of West Nusa Tenggara are characterized on the MMI VII-VIII intensity scale, and only a small part is characterized on the V-VI MMI intensity scale. The implications of the results of this research are useful in disaster mitigation, so it is hoped that there will be a reduction in disaster risk.